Synthesis, Characterization and Thermal Study of Some Transition Metal Complexes Derived from Quinoxaline-2,3-Dione - Musa, Taghreed M.; A.Al-jibouri, Mahmoud Najim; Abbas, Bayader Fadhil (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The present paper describes the synthesis and structural studies of new transition metal complexes of cobalt(II), nickel(II), copper(II) and cadmium(II) with two bi dentate ligands derived from quinoxaline-2,3-dione. The two ligands were fully identified by elemental analyses, FT-IR, NMR and UV-Visible spectra. The metal complexes of  Co(II), Ni(II), Cu(II) and Cd(II) were isolated in the solid state after reactions of their metal chlorides with the ligands in 2:1 mole ratio. The isolated solid metal complexes were characterized with the help of elemental analyses, NMR, FT-IR and UV-Visible spectra. As well as the thermal stability of the coordinated quinoxaline polymers were tested by TG-DSC analysis and it is found that cleavage of terminal moiety was investigated, the strong coordinated bonds between oxygen donor atoms in L1 while nitrogen donor atoms of quinoxaline ring in the L2 with the metal ions. Furthermore, the thermal stability of cobalt(II), nickel(II), copper(II) and Cd(II) complexes were screened by TG-DSC analysis and the results helped us in the investigation of the proposed structure of the prepared complexes in the formula [M(L)2Cl2].XH2O and [Cd(L)2]Cl2 where L= L1 and L2  ligands derived from quinoxaline-2,3-dione.